Residential greenness and long-term mortality among patients who underwent coronary artery bypass graft surgery - Sadeh, Maya; Fulman, Nir; Agay, Nirit; Levy, Ilan; Ziv, Arnona; Chudnovsky, Alexandra; Brauer, Michael; Dankner, Rachel (Epidemiology, 2024)
Background: - Studies have reported inverse associations between exposure to residential greenness and mortality. Greenness has also been associated with better surgical recovery. However, studies have had small sample sizes and have been restricted to clinical settings. We investigated the association between exposure to residential greenness and all-cause mortality among a cohort of cardiac patients who underwent coronary artery bypass graft (CABG) surgery. - Methods: - We studied this cohort of 3,128 CABG patients between 2004 and 2009 at seven cardiothoracic departments in Israel and followed patients until death or 1st May 2021. We collected covariate information at the time of surgery and calculated the patient-level average normalized difference vegetation index (NDVI) over the entire follow-up in a 300 m buffer from the home address. We used Cox proportional hazards regression models to estimate associations between greenness and death, adjusting for age, sex, origin, socioeconomic status, type of hospital admission, peripherality, air pollution, and distance from the sea. - Results: - Mean age at surgery was 63.8 ± 10.6 for men and 69.5 ± 10.0 for women. During an average of 12.1 years of follow-up (37,912 person-years), 1,442 (46%) patients died. A fully adjusted Cox proportional hazards model estimated a 7% lower risk of mortality (HR: 0.93, 95% CI = [0.85, 1.00]) per 1 interquartile range width increase (0.04) in NDVI. Results were robust to the use of different buffer sizes (100 m-1,250 m from the home) and to the use of average NDVI exposure during the first versus the last 2 years of follow-up. - Conclusions: - Residential greenness was associated with lower risk of mortality in CABG patients.
Gesehen am 31.01.2024